Strategy For Choosing A College To Continue Further Studies For Students In Batubara Regency - Sulistyawati, Sri; Alamsyah, Bhakti; Sofiyan, Sofiyan; Tua Siregar, Robert; Setyawan, Iwan (CV. Inara, 2025)
College is a more complex gateway and focuses on a particular field of expertise. Therefore, it is only right that in finding a college there are many measuring indicators, depending on the priorities of each individual. Although education is not only obtained in the classroom, the way to explore students' potential needs to be done because the world of work which is a phase of life that actually depends on what they currently have. The Community Service that we carried out in Batubara Regency in collaboration with the Regional Education Office Branch V of Batubara Regency, the event